Resgate do Teorema de Dandelin no estudo de cônicas com o geogebra - Monteiro, Rubens Marinho (2014)
The purpose of this work is to make the rescue of Dandelin‘s theorem in the study of conical. The idea is to present how Dandelin used spheres and cones to show that the curves that arise when cutting a conical surface by a plane are: ellipse, hyperbole, or parable. We will define the general equation of a conic by its eccentricity, as well as the relationship between the geometric and algebraic concept. We will do an analysis of how the book “Novo Olhar - Matem´atica” of Joamir Souza, work adopted by the state Department of Education of Esp´irito Santo for the students of the 3rd level of high school, is the approach of the conical theme. It is also reported in this work a collection of experiences and activities elaborated in the software Geogebra and Winplot that were discussed in the disciplines of MA35, MA36 and MA23 whose character is to contextualize and give applications to conical.